Virus Wannacry dalam Teks Berita: Analisis Wacana Kritis atas Laman Kemkominfo, Kompas.com, dan Jawapos.com - Izhatullaili, Izhatullaili (UI Scholars Hub, 2018)
Critical Discourse Analysis is a study that analyzes language usage in terms of linguistic features and a social practice. Each type of mass media shows a different tendency in conveying information through the language it uses. Likewise, there are some differences between government and non-government media as well. The data in this study were obtained by collecting texts related to WannaCry virus news taken from the Ministry of Communication and Information Technology, Kompas.com and JawaPos.com. Abductive inferences technique was used to draw conclusions by connecting one text to other texts. The different tendencies in media’s linguistic features and ideologies were described using critical discourse analysis and Fairclough’s three interrelated analysis processes (i.e. the dimension of text description, the dimension of discourse practice by textual interpretation, and the dimension of socio-cultural by text explanation). The results of this study showed that the three media had some differences in both of their linguistic features and ideology.